GEOLOGY AND GEOMORPHOLOGY OF THE “ROSANDRA” VALLEY FOR A CULTURAL ENHANCEMENT - Cucchi, Franco; Mereu, Alessio; Oberti, Sara; Piano, Chiara; Rossi, Anna; Zini, Luca (Alpine and Mediterranean Quaternary, 2005)
F. Cucchi et al., Geology and Geomorphology of the “Rosandra” Valley for a Cultural Enhancement. (IT ISSN 0394-3356, 2005). The Rosandra Valley is located near Trieste (Italy), on the border of Classical Karst, and is a canyon-like depression excavated in tertiary limestone. The origin of the valley is mainly due to presence of faults and overthrusts and different attitude to erosion between limestone and marls, which makes it a beautiful example of lithological and structural control on morphogenesis. Furthermore, its slopes are interested by extended and mature underground karst phenomena that contribute to making the whole hydro-structure more interesting. The valley is also remarkable for its local vegetation, due to its particular climatic conditions, and to its prehistoric and historical value, stemming from its geographic location.